Numerical simulation of the effects of experimental error on the higher harmonic components of Fourier transformed AC voltammograms - Gavaghan, D; Bond, A (2006)
In this simulation study we investigate the effects of realistic levels of random and systematic experimental error in higher harmonics detected by Fourier transformed AC voltammetry for a reversible process. We show that by analyzing in the frequency domain results that are collected in the time domain, we can achieve a very large reduction in the magnitude of random (Gaussian) noise, and complete elimination of the systematic error introduced by mains frequency in both the small and large amplitude cases. As a consequence, we confirm experiment